2013
DOI: 10.1136/bmjopen-2013-002926
|View full text |Cite
|
Sign up to set email alerts
|

Improving continence services for older people from the service-providers’ perspective: a qualitative interview study

Abstract: ObjectiveTo examine in depth the views and experiences of continence service leads in England on key service and continence management characteristics in order to identify and to improve our understanding of barriers to a good-quality service and potential facilitators to develop and to improve services for older people with urinary incontinence (UI).DesignQualitative semistructured interviews using a purposive sample recruited across 16 continence services.Setting3 acute and 13 primary care National Health Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 51 publications
1
19
0
Order By: Relevance
“…Other research has found a need for improvements in service capacity, for example, regarding staff training and inter‐service collaboration (Orrell et al . ). Importantly, the national audit did not capture the views of service users on why they sought help.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Other research has found a need for improvements in service capacity, for example, regarding staff training and inter‐service collaboration (Orrell et al . ). Importantly, the national audit did not capture the views of service users on why they sought help.…”
Section: Introductionmentioning
confidence: 97%
“…A UK national audit of continence care for older people, which sampled acute and rehabilitation hospitals, found poorly integrated continence services and an inconsistent screening for UI or adequate assessment by service providers (Wagg et al 2010). Other research has found a need for improvements in service capacity, for example, regarding staff training and inter-service collaboration (Orrell et al 2013). Importantly, the national audit did not capture the views of service users on why they sought help.…”
mentioning
confidence: 97%
“…Attitudes towards UI, both in general (i.e. in society) and within the healthcare setting, have been found to be partially negative (Orrell, McKee, Dahlberg, Gilhooly, & Parker, ). The routine management of incontinence (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the delivery and organisation of continence services in primary and secondary care should be scrutinised [ 28 ]. Clear referral pathways and investment in capacity, for example, through the provision of more trained staff and a higher profile for continence care within medical training, have been identified as possible facilitators for the delivery of high-quality and equitable continence services.…”
Section: Discussionmentioning
confidence: 99%